FoMO and Social Media: Constructing Tennis as a Middle-Class Lifestyle Trend in Jakarta - Indah Fajar Rosalina; Kristanti Agustina; Suswinda Ningsih (Universitas Multimedia Nusantara, 2025)
This study examines the phenomenon of Fear of Missing Out (FoMO) on social media and its influence on the rise of tennis as a lifestyle trend among Jakarta’s middle class. Using a qualitative phenomenological approach, data were gathered through in-depth interviews, observation, and document analysis involving eight participants. The findings reveal that platforms like Instagram and TikTok shape tennis not only as a recreational activity but also as a symbol of status, health, and social identity. FoMO drives participation by creating pressure to keep up with curated digital trends. Urban middle-class individuals engage in tennis to maintain visibility, relevance, and a cohesive lifestyle image online. However, this trend is marked by class distinctions: while upper-middle-class individuals actively participate, those from lower-middle backgrounds often face symbolic exclusion due to the high costs of equipment, court access, and stylish sportswear. The study identifies two main FoMO motivations—status-driven and wellness-oriented—both amplified by social media’s visual culture. Emerging strategies to reduce FoMO include media literacy, and a return to authentic offline experiences. By applying Veblen’s theory of conspicuous consumption and Baudrillard’s sign-value, this research contributes to understanding the intersections of lifestyle, identity, and social class in Jakarta’s digital urban culture.